2015
DOI: 10.1007/s10875-015-0225-6
|View full text |Cite
|
Sign up to set email alerts
|

A Multiplex Kindred with Hennekam Syndrome due to Homozygosity for a CCBE1 Mutation that does not Prevent Protein Expression

Abstract: Collagen and calcium-binding EGF domain-containing protein 1 (CCBE1) bi-allelic mutations have been associated with syndromes of widespread congenital lymphatic dysplasia, including Hennekam Syndrome (HS). HS is characterized by lymphedema, lymphangiectasia, and intellectual disability. CCBE1 encodes a putative extracellular matrix protein but the HS-causing mutations have not been studied biochemically. We report two HS siblings, born to consanguineous parents of Turkish ancestry, whose clinical phenotype als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“… 35 Previous studies found that CCBE1 is a secreted molecule involved in lymphangiogenesis, 14 , 36 and congenital CCBE1 mutations have been shown to cause Hennekam syndrome. 36 , 37 To confirm the relationship between CCBE1 expression and prognosis and clinicopathological features of CRC, 204 cases of CRC tissues were stained to analyze. IHC results showed that high expression of CCBE1 was observed in 55.4% (113/204) CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Previous studies found that CCBE1 is a secreted molecule involved in lymphangiogenesis, 14 , 36 and congenital CCBE1 mutations have been shown to cause Hennekam syndrome. 36 , 37 To confirm the relationship between CCBE1 expression and prognosis and clinicopathological features of CRC, 204 cases of CRC tissues were stained to analyze. IHC results showed that high expression of CCBE1 was observed in 55.4% (113/204) CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Homozygosity mapping has identified CCBE1 gene variants to be a cause of HKLLS1 . So far, at least 12 different CCBE1 variants have been reported in at least seventeen probands/families …”
Section: Discussionmentioning
confidence: 99%
“…Of the various forms of primary lymphedema, CCBE1 mutations appear to be predominantly causative for Hennekam syndrome [Alders et al, ]. Fewer than 50 patients with Hennekam Syndrome have been reported in the literature to date, with 25–29% of those having biallelic CCBE1 coding mutations [Alders et al, ; Jackson et al, ] and 20% having biallelic FAT4 mutations. Fotiou et al [] recently reported biallelic mutations in PIEZO1 can result in generalized lymphatic dysplasia, phenotypically similar to Hennekam syndrome.…”
Section: Discussionmentioning
confidence: 99%